Spatial variation characteristics and influencing factors of sediment connectivity in the black soil region of northeast China - Wang Jia-nan; Fan Hao-ming; Jia Yan-feng (Geoderma, 2024)
Connectivity has become an important indicator of the sediment transfer potential through sediment sources to catchment sinks. Connectivity plays a vital role in investigating the rate of soil erosion caused by runoff and sediment output across the watershed landscape. However, there have been few quantitative studies on the spatial variations in sediment connectivity in the black soil region of Northeast China. Seven classic watersheds in the northeast black soil region were selected to discover spatial variations in sediment connectivity and their influencing factors. The connectivity index (IC) was used to study the spatial variation of sediment connectivity, and the weight of IC was calculated using the vegetation cover management factor (C), which reflected the influence of human activities on the soil erosion process caused by cultivated land expansion and encroachment of forest grassland. The redundancy analysis method (RDA) was used to determine the main factors affecting the spatial variation of IC. The results showed that IC decreased from north (0.45) to south (0.12). The spatial variations of watersheds in sediment connectivity showed significant spatial heterogeneity. IC was correlated with topographic, climatic, and artificial management characteristics at 0.01 or 0.05 levels except soil structural index; RDA results showed that topography and human activities were the main factors affecting sediment connectivity. Topographic and climatic factors explained more sediment connectivity changes in the southern watersheds than in the northern watersheds, while the human activities factor explanation was the opposite of topographic factors. Human activities refer to changes in vegetation cover and soil structure and properties resulting from human logging and farming that affect sediment connectivity.